1986
DOI: 10.1128/iai.54.3.626-634.1986
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic interrelationship between endoflagella of Treponema phagedenis biotype Reiter and Treponema pallidum (Nichols): molecular characterization of endoflagellar proteins

Abstract: Purified endoflagella from nonpathogenic Treponema phagedenis bioptye Reiter were characterized biochemically and compared antigenically with the endoflageilar proteins of Treponema pallidum. T. phagedenis biotype Reiter endoflagella were dissociated into constituent polypeptides by incubation under conditions which disrupt noncovalent bonds. Chymotrypsin peptide maps of T. phagedenis biotype Reiter endoflageliar proteins revealed that the 37and 33-kilodalton (kDa) major components shared significant homology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
26
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 36 publications
5
26
0
Order By: Relevance
“…Many investigators have described axial fiagellar polypeptides with similar molecular sizes (8,13,14,19,20). T.patltdutn strain Nichols and 77 phagedenis have an additional flagellar protein with an approximate molecular weight of 38 kDa (2,13,17,19,20). The two ATCC strains of 77 dentieola possessed the 34 kDa P3 and 38 kDa PI 1 axial flagellar proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many investigators have described axial fiagellar polypeptides with similar molecular sizes (8,13,14,19,20). T.patltdutn strain Nichols and 77 phagedenis have an additional flagellar protein with an approximate molecular weight of 38 kDa (2,13,17,19,20). The two ATCC strains of 77 dentieola possessed the 34 kDa P3 and 38 kDa PI 1 axial flagellar proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Discontinuous SDS-PAGE was conducted on the basis of the method of Laemmli as reported previously (II). A mixture of each bacterial suspension (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) fig of protein per lane) and solubilization buffer was heated at 100 C for 5 min and applied to 1-or 2-mmthick SDS-10% acrylamide gels. A total of 13 polypeptides were selected on the basis of individual quantity, clear separation from neighboring protein bands and exclusion of the antigens with apparently similar molecular sizes.…”
Section: Sds-page and Polyclonai Antisera Productionmentioning
confidence: 99%
“…Recent studies performed in our laboratory have demonstrated the presence of T. pallidum specific antigenic determinants on the 37-, 34.5-, 33-, and 31-kDa endoflagellar polypeptides (3). In view of the demonstrated cross-reactivity that exists among the endoflagella of T. pallidum, host indigenous nonpathogenic treponemes (3,4,13,24,29), and other pathogenic spirochetes, including Borrelia burgdorferi (18; Lovett et al, unpublished data), and Leptospira interrogans (Lovett et al, unpublished data), these unique T. pallidum endoflagellar epitopes could well provide a more specific and sensitive serodiagnostic antigen for the detection of syphilis.…”
mentioning
confidence: 94%
“…Endoflagella are major protein and antigenic constituents of T. pallidum which are recognized by antibody early in and throughout the course of the disease (11,12,26,27). Serodiagnostic studies in which workers have used endoflagella prepared from Treponema phagedenis biotype Reiter, whose endoflagella share considerable antigenic cross-reactivity with the endoflagella of T. pallidum (3,4,13,24,29), have shown similar degrees of sensitivity and specificity compared with the standard T. pallidum serodiagnostic tests currently in use (27). Recent studies performed in our laboratory have demonstrated the presence of T. pallidum specific antigenic determinants on the 37-, 34.5-, 33-, and 31-kDa endoflagellar polypeptides (3).…”
mentioning
confidence: 99%
“…Purified axial flagella of T. pallidum Nichols and T. phagedenis biotype Reiter consist of at least two proteins with approximate molecular sizes of 33 kDa to 34 kDa and 37 kDa to 39 kDa, although their reported molecular sizes are not coincident among investigators (10,11). Limberger and Charon also reported a 34-kDa common antigen in several treponemes (7).…”
Section: Strainsmentioning
confidence: 99%